KERETA SINGO BARONG DI KERATON KASEPUHAN CIREBON - Sumino Sumino (Corak : Jurnal Seni Kriya, 2012)
This study to look at the changes the meaning of Singo Barong in the context of the past asunderstood by the public Cirebon in the present. In the time, the train experienced a period oftransit which to change the context in which the material or object of art will have meaning.As a result of the frequent occurrence of changes in the context of the meanings are oftensubject to change. It is an art object in transition, experiencing a change of meaning as aresult of changes in context. Change of meaning will evoke an emotional response whencrossing cultural boundaries.Reading of documents or artifacts that are relevant necessary to achieve a deeper meaningand detail. Therefore anthropological perspective that links production and consumption ofartifacts are not separated from the question of the culture, politics, religion and others.Borrowing the theory of "processual relativism" Svasek will bring an understanding of the artmaterial in a different time and space. At least not with borrowed this theory will be obtainedthe values behind the train characteristics. By finding the characteristics at a certain time andspace will be acquired meaning, then what meaning it will be reviewed and compared. Suchway of thinking is more easy to see the socio-cultural change at both the pattern of thought orsocial institutions Kasepuhan Cirebon palace.Singo Barong train its existence is equivalent to other objects stored in the MuseumKasepuhan Cirebon, such as gamelan, batik cloth, weapons, and so forth. Artifacts have thesame weight value when used as a tool in the ritual. But the context has a different meaning,is associated with the constituent. From time to time, the meaning is changed, both in socialand cultural areas. Religious meaning at the time of the kings was in power changed thefulfillment of the ritual or ceremonial, then change as the fulfillment of the economy andtourism.Keywords: Train Singo Barong, Svasek, Changes